Genotypic and phenotypic diversity of Mycobacterium tuberculosis strains in patients with concomitant pulmonary and extra-pulmonary tuberculosis - Peters, Remco P.H. (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.